Evaluation of Semi-Aerobic Plant Waste Composting System in a Manufacturing Industry in Surabaya: Evaluasi Sistem Pengomposan Semi-Aerob Sampah Organik Sisa Tanaman pada Industri Manufaktur di Surabaya - Arum Retno Dwi Lestari; Aussie Amalia (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The management of plant-based organic waste in industrial environments is an important component of waste reduction efforts and the implementation of sustainable environmental management principles. A manufacturing industry in Surabaya manages plant residue waste through an internal composting system that has not fully applied controlled aerobic composting principles. This activity aims to evaluate the semi-aerobic composting system implemented, particularly in terms of process flow, composting duration, and the quality of the resulting compost compared to applicable standards and regulations. The method used was a descriptive qualitative approach with an evaluative framework, conducted through field observations, interviews, and monitoring of process parameters such as temperature and pH. The results indicate that the composting process required a longer duration than the ideal timeframe due to the absence of material shredding and limited aeration, which reduced microbial activity during decomposition. These conditions affected compost quality, resulting in non-uniform maturity and characteristics that did not fully meet compost maturity criteria. This evaluation provides an overview of the existing composting system and serves as a basis for developing improvement recommendations to enhance process efficiency and compost quality in accordance with applicable composting standards.